Intertextuality of the Symbolism of Mountain Destruction in the Qur'an and the Bible - Binti Khabibatur (Tilawah: Journal of Al-Qur'an Studies, 2025)
This study discusses the phenomenon of mountain destruction from the perspective of two Abrahamic holy books, namely the Qur'an and the Bible. The narratives of both books explain that the destruction of mountains on the last day of time is a powerful symbol in describing cosmic events on the Day of Judgment. The destruction of mountains in the Qur'an is described in detail and visually, such as dust, flying feathers, and mirages. Meanwhile, in the Bible, the destruction of mountains tends to be symbolic, indicating God's wrath. The methodology used is a literature review with a qualitative, chronological, descriptive, and analytical approach, with primary sources from sacred texts and relevant literature. Kristeva emphasizes that texts are interconnected and form shared meaning. The results of the research indicate that both books, regarding the destruction of mountains, are not merely physical visualizations. However, the destruction of mountains carries meaning as a symbol of God's power and as a sign or reminder for all humanity.